(untitled) (Zaporizhzhia Historical Review, 2019)
The article presents the periodization of modern Ukrainian historiography development devoted to the Holodomor (Famine) of 1921–1923 on the territory of Ukraine. It is proved that modern historiography has a number of features that give grounds to distinguish three periods in its development. The first period is 1991 – the end of the 1990’s; the second one is from 2000 to 2019. Each period is distinguished by new scientific approaches, a deeper understanding of the history of the tragedy, the introduction of new archival documents for scientific circulation and logical that, at last, the historiography of the topic replenishes the works of strictly historiographical content, the appearance of which became possible thanks to accumulated historical facts, published collections of documents and new developments of regional content.